2022
DOI: 10.1038/s41467-022-29696-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sub-kilobase chromatin topology reveals nano-scale regulatory interactions with variable dependence on cohesin and CTCF

Abstract: Enhancers and promoters predominantly interact within large-scale topologically associating domains (TADs), which are formed by loop extrusion mediated by cohesin and CTCF. However, it is unclear whether complex chromatin structures exist at sub-kilobase-scale and to what extent fine-scale regulatory interactions depend on loop extrusion. To address these questions, we present an MNase-based chromosome conformation capture (3C) approach, which has enabled us to generate the most detailed local interaction data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 73 publications
5
55
0
Order By: Relevance
“…When affected, the altered E–P/P–P interactions only result in moderate expression changes of the underlying genes. Our findings, together with other evidence 63 , 68 , allow us to distinguish and/or eliminate several models of E–P interactions previously assigned to these ubiquitous structural proteins (Fig. 8 ).…”
Section: Discussionsupporting
confidence: 60%
“…When affected, the altered E–P/P–P interactions only result in moderate expression changes of the underlying genes. Our findings, together with other evidence 63 , 68 , allow us to distinguish and/or eliminate several models of E–P interactions previously assigned to these ubiquitous structural proteins (Fig. 8 ).…”
Section: Discussionsupporting
confidence: 60%
“…Loop extrusion had been thought of as a key controller of E-P interactions (Symmons et al 2014 ). However, recent studies found that cohesin and CTCF are not required for E-P interactions through acute degradation or deletion of CTCF motifs (Aljahani et al 2022 ; Chakraborty 2022 ). Furthermore, CTCF and a portion of cohesin in yeast interact with interactors or chromatin through phase separation (Ryu et al 2021 ; Wei et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the epiblast and in neuronal tissues, CTCF-mediated loops are not required for Sox2 promoter and distal enhancer contact or for Sox2 expression, but high-affinity enhancer-promoter interactions themselves can bypass CTCF/cohesin-mediated insulation and function in maintaining phenotypic robustness [69] . By generating contact matrices at a 20 bp resolution with an extension of the MNase-based 3C approach, also known as Tiled-Micro-Capture-C (Tiled-MCC), it has been shown that within cis -regulatory elements with distinct internal nanoscale structures, local insulation is dependent on CTCF but independent of cohesion [70] . Specifically, the depletion of cohesin subtly reduces enhancer–promoter contacts and leads to a small decrease in gene expression, but CTCF depletion can induce rewiring of interactions and ectopic gene activation in some cases, instead of generally reducing interactions between certain enhancers and promoters [70] .…”
Section: Topological Insulators and Chromatin Mediators As A Function...mentioning
confidence: 99%
“…By generating contact matrices at a 20 bp resolution with an extension of the MNase-based 3C approach, also known as Tiled-Micro-Capture-C (Tiled-MCC), it has been shown that within cis -regulatory elements with distinct internal nanoscale structures, local insulation is dependent on CTCF but independent of cohesion [70] . Specifically, the depletion of cohesin subtly reduces enhancer–promoter contacts and leads to a small decrease in gene expression, but CTCF depletion can induce rewiring of interactions and ectopic gene activation in some cases, instead of generally reducing interactions between certain enhancers and promoters [70] . Furthermore, a recent study showed that a TAD physically separates Zfp42 and Fat1 , which have distinct local enhancers that drive their independent expression in ESCs (embryonic stem cells), but this separation is driven by chromatin activity independent of CTCF/cohesion [71] .…”
Section: Topological Insulators and Chromatin Mediators As A Function...mentioning
confidence: 99%